Acidic tumor microenvironment and pH-sensing G protein-coupled receptors - Justus, Calvin R.; Dong, Lixue; Yang, Li V. (Frontiers in Physiology, 2013)
The tumor microenvironment is acidic due to glycolytic cancer cell metabolism, hypoxia, and deficient blood perfusion. It is proposed that acidosis in the tumor microenvironment is an important stress factor and selection force for cancer cell somatic evolution. Acidic pH has pleiotropic effects on the proliferation, migration, invasion, metastasis, and therapeutic response of cancer cells and the function of immune cells, vascular cells, and other stromal cells. However, the molecular mechanisms by which cancer cells and stromal cells sense and respond to acidic pH in the tumor microenvironment are poorly understood. In this article the role of a family of pH-sensing G protein-coupled receptors (GPCRs) in tumor biology is reviewed. Recent studies show that the pH-sensing GPCRs, including GPR4, GPR65 (TDAG8), GPR68 (OGR1), and GPR132 (G2A), regulate cancer cell metastasis and proliferation, immune cell function, inflammation, and blood vessel formation. Activation of the proton-sensing GPCRs by acidosis transduces multiple downstream G protein signaling pathways. Since GPCRs are major drug targets, small molecule modulators of the pH-sensing GPCRs are being actively developed and evaluated. Research on the pH-sensing GPCRs will continue to provide important insights into the molecular interaction between tumor and its acidic microenvironment and may identify new targets for cancer therapy and chemoprevention.